2003
DOI: 10.1152/ajpendo.00035.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific p38 MAP kinase activation following trauma-hemorrhage: involvement of testosterone and estradiol

Abstract: . Sex-specific p38 MAP kinase activation following trauma-hemorrhage: involvement of testosterone and estradiol. Am J Physiol Endocrinol Metab 285: E189-E196, 2003; 10.1152/ajpendo.00035. 2003.-Although immune functions are markedly depressed in males and not in proestrous females following traumahemorrhage (T-H), the mechanisms responsible for the divergent responses remain unknown. Because sex steroids modulate the activation of p38, our aim was to determine whether differences in the activation of p38 by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 36 publications
5
29
0
1
Order By: Relevance
“…MAPKs play an important role in the regulation of macrophage activation as well as other functions (4,(37)(38)(39)(40)(41)(42). Moreover, the production of various cytokines by macrophages involves MAPK signal transduction pathways (38,(43)(44)(45)(46). The present results demonstrate that p38, ERK1/2, and JNK were activated in keratinocytes after trauma-hemorrhage, a finding that suggests that the stress of trauma-hemorrhage per se caused the activation of some signaling pathways leading to MAPKs.…”
Section: O V E M B E R -D E C E M B E R 2 0 0 8 T R a U M A -H E M O supporting
confidence: 57%
“…MAPKs play an important role in the regulation of macrophage activation as well as other functions (4,(37)(38)(39)(40)(41)(42). Moreover, the production of various cytokines by macrophages involves MAPK signal transduction pathways (38,(43)(44)(45)(46). The present results demonstrate that p38, ERK1/2, and JNK were activated in keratinocytes after trauma-hemorrhage, a finding that suggests that the stress of trauma-hemorrhage per se caused the activation of some signaling pathways leading to MAPKs.…”
Section: O V E M B E R -D E C E M B E R 2 0 0 8 T R a U M A -H E M O supporting
confidence: 57%
“…Previous findings suggest that depletion of 5␣-dihydrotestosterone in castrated males is responsible for the improved immune responses after traumahemorrhage in those animals (2). In this respect, treatment of castrated males with 5␣-dihydrotestosterone resulted in suppressed splenic and peritoneal M⌽ cytokine responses after trauma-hemorrhage comparable to noncastrated male mice (7,8). Thus one would speculate that the testosterone derivate 5␣-dihydrotestosterone also plays a pivotal role for suppressing MHC II (Ia) expression.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies suggest a gender-specific difference in activation of p38 mitogen activated protein kinase via phosphorylation. 16,27 Evidence of oxidant injury appears rapidly after resuscitation from cardiac arrest, and activation of characteristic metabolic cascades responsible for reperfusion injury and the accompanying inflammatory response are to be expected. 1,2 Observational clinical studies in small series of patients have demonstrated elevated proinflammatory cytokine levels among individuals resuscitated from cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%